Extracurricular Management to Improve the Quality of Student Services at an Islamic Senior High School in Indonesia - Dinda Putri; Muhammad Fadhli (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the management of extracurricular activities in improving the quality of student services at Madrasah Aliyah Negeri 2 Model Medan by using the SERVQUAL framework, which includes the dimensions of tangibles, reliability, responsiveness, and assurance. This study uses a qualitative approach with a case study design. Research participants include the head of the madrasah, the vice principal for student affairs, extracurricular activity supervisors, and students selected purposively. Data collection techniques were conducted through semi-structured interviews, non-participant observation, and documentation study. Data analysis used the model of Miles, Huberman, and Saldaña, while data validity was ensured through triangulation and member checking. The results of the study indicate that the management of extracurricular activities at Madrasah Aliyah Negeri 2 Model Medan is able to improve the quality of student services. The tangible dimension is reflected in the availability of facilities, structured schedules, budget support, and the presence of mentors. The reliability dimension is seen from the consistency in activity implementation, clarity of organizational structure, and mentor commitment. The responsiveness dimension is demonstrated through the openness of the madrasah in responding to the needs and aspirations of students. Meanwhile, the assurance dimension is apparent from the competence of mentors, continuous guidance, as well as the existence of program monitoring and evaluation.